Pementasan Tong Bing Xiang Lian Oleh Dao Sheng Methodist Drama Troupe. - Ngu, Li Chuo (Universiti Malaysia Sarawak (UNIMAS), 2020)
This research aims to clarify six units of Aristotle's which are consist of the Plot, Character, Idea, Language, Music and Spectacle found in the Tong Bing Xiang Lian theatre staging held at the East Campus Multipurpose Hall, University of Malaysia Sarawak. This research is a qualitative study. The research method used to obtain information is through primary and secondary data. The primary data that used are observation, interview, survey form and video recording. Then, the secondary data that used are library reference and journal. In conclusion, Tong Bing Xiang Lian theatre can be categorized as a theatre because it has six elements of Aristotle.